2001
DOI: 10.1074/jbc.m103320200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Properties of a Novel Intracellular (Mitochondrial) ATP-sensitive Potassium Channel in Brain

Abstract: Protection of heart against ischemia-reperfusion injury by ischemic preconditioning and K ATP channel openers is known to involve the mitochondrial ATPsensitive K ؉ channel (mitoK ATP ). Brain is also protected by ischemic preconditioning and K ATP channel openers, and it has been suggested that mitoK ATP may also play a key role in brain protection. However, it is not known whether mitoK ATP exists in brain mitochondria, and, if so, whether its properties are similar to or different from those of heart mitoK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
199
2
29

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(238 citation statements)
references
References 56 publications
8
199
2
29
Order By: Relevance
“…Immunohistochemical studies showed that Kir6.2 subunits are mainly located in the somata and dendrites of the central neurons [92,93,96] . Mitochondrial K ATP channels are also found in the rat brain, and the expression level of Kir6.1 (per milligram of mitochondrial protein) is six to seven times higher than that in the heart and liver [12] . Radioligand binding studies showed that regional expression of K ATP channels in the brain showed different affinities to sulfonylureas [97] .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Immunohistochemical studies showed that Kir6.2 subunits are mainly located in the somata and dendrites of the central neurons [92,93,96] . Mitochondrial K ATP channels are also found in the rat brain, and the expression level of Kir6.1 (per milligram of mitochondrial protein) is six to seven times higher than that in the heart and liver [12] . Radioligand binding studies showed that regional expression of K ATP channels in the brain showed different affinities to sulfonylureas [97] .…”
Section: Introductionmentioning
confidence: 97%
“…Kir6.1-based channels have a smaller unitary conductance than Kir6.2 subtype channels [27] . Kir6.2 subunits are found in plasmalemmal membranes (cell surface membranes) [12,20,27,29,32] . Most functional K ATP channels contain the Kir6.2 subunit; thus, the heterogeneity observed between different K ATP channels mainly arises from the differential expression of the SUR regulatory subunits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the brain, however, the role of mitochondrial K ATP channels in ischemic tolerance remains to be elucidated, although inhibition of preconditioning-induced protection by a nonspecific antagonist acting on both surface and mitochondrial K ATP channels has been reported in global ischemia (Heurteaux et al, 1995). Recently, a mitochondrial K ATP channel proteins were partially purified from rat brain mitochondria and exhibited ligand-binding properties similar to those of heart mitochondrial K ATP channels (Bajgar et al, 2001). The amount of mitochondrial K ATP channels in the brain was reported to be much higher than in the heart (Bajgar et al, 2001), suggesting the possibility that mitochondrial K ATP channels play an important role in neural function.…”
mentioning
confidence: 99%
“…Pore opening can be stimulated by inorganic phosphate, caspases, SH-reagents, cell exhaustion by reduced glutathione, formation of active forms of oxygen, uncoupling of oxidative phosphorylation, rise in Ca 2+ content in the cytoplasm, effect of ceramide, depletion of the mitochondrial ATP pool, etc. [24,27,28].…”
Section: Bodymentioning
confidence: 99%